A Content Analysis on Discourses About Influence of Religion on the 2023 Presidential Election in Nigeria - Onyenekwe, Ogochukwu; Okpara, Chioma (ESUT JOURNAL OF SOCIAL SCIENCES, 2023)
In most countries of the world, certain discourses top the media agenda prior to national elections. This is the case in Nigeria where such discourses on religion or ethnicity still play a major role capable of swinging election victory in any direction.This study examined the discourses surrounding religious story headlines preceding 2023 presidential election in Nigeria using content analysis of three prominent and widely read newspapers in Nigeria. The purpose of the study was to identify how religion influenced the discourse preceding the 2023 presidential election. Data was collected by using coding sheets to study the news headlines of three (3) major national online newspapers namely ThisDay online newspaper, Punch online newspaper and Guardian online newspaper for a period of ten (10) months (January, 2021 to October, 2021). Results from the analysed data showed that the newspapers within the period under study had a number of news story headlines regarding the upcoming 2023 elections from diverse angles. Out of the 120 editions of the first quarter in the study, story headlines with religious discourse featured once (0.83%) in ThisDay online newspaper but not in Punch nor Guardian online newspapers. In the second quarter, out of the 123 editions, story headlines on religious discourse featured twice (1.63%) in ThisDay online edition and once in Punch (0.81%) online newspaper but none in Guardian online newspaper. In the third quarter, out of 61 editions, story headlines on religious discourse featured six times (9.84%) in Punch online newspaper and once (1.64%) in Guardian online newspaper but none in ThisDay online newspaper. The study concludes that much attention was not given by the media to religious discourses pertaining to the 2023 presidential elections. This may suggest that the Editors of such newspapers did not consider granting much attention to religious discourses during this time due to editorial policy on such perceived volatile subjects in a perceived secular Nigeria or not yet the ripe time for agenda setting.